Use Of High Capacity Grouted Tension Piles Installed Vibration Free And Soil Displacing - Peter de Kort (Deep Foundations Institute, 2008)
Tunnels in urban areas generally require deep excavations in soils under the groundwater table. In The Netherlands uplift loads are generally taken by piles installed into dense sand layers, which are hard to penetrate. To avoid nuisance and damage to the environment, piles often need to be installed using vibration free methods, which also have the advantage of low noise levels during installation. Drilling piles and obtaining a high uplift resistance is a contradiction in itself. Franki has adopted several installation methods based on the injection of grout during drilling and/or post grouting to overcome the difficulty of hard layers. This report presents two projects, situated in Rotterdam and Sneek, where vertical tension piles in floors, subject to high uplift loads, have been used. It also explores a project in Zeebrugge (Belgium), where tension piles are installed at an inclination of 1:1 to anchor a diaphragm wall for a quay construction. Test results presented in this report show, that vibration free and soil displacing piles can be installed in very dense sand layers and that a high uplift resistance can be achieved. It is also shown, that a variety of installation methods is available, even in limited space.